ECOFEMINISM OF FORESTRY CONSERVATION IN RIAU - Nailufar, Faza Dhora; Hidayaturahmi, .; Rahmawati, Aulia (KnE Social Sciences, 2022)
In the last 18 years, Riau Province, especially Pekanbaru and its surroundings, has often been surrounded by smoke from forest fires. Based on National Board and Disaster Management, Riau is the province with the largest forest fires. There were 49,266 hectares of land burned with 90 hotspots detected until August 2019. The effect of it was the air pollution index in Pekanbaru and its surroundings has reached red degrees. This condition is very dangerous, especially for vulnerable groups such as women, pregnant women, elderly group and children. The central and local government have taken many actions every year, but still not sufficient to protect public health, especially vulnerable groups. So far, women and children have been forced to inhale the smoke intensively without any protective equipment (N95 masks) or proper shelters in case of forest fires. The children were forced not to go to school for weeks, because the classrooms were not equipped with air-conditioned rooms and air purifiers. Several studies have found that smoke-contaminated air, soil and food are very bad for health before and after birth. Toxic substances inhaled by pregnant women can interfere with their health and interfere with the nutrition and oxygen flow of the fetus. Another study also found that exposure to Indonesia’s forest fires in late 1997 caused more than 15,600 child, infant and fetal deaths, meaning children’s survival rates decreased by 1.2 percentage points due to exposure to toxic fumes. A child’s nutrition and health can be directly compromised after inhaling toxic fumes or ingesting them in contaminated raw food. In addition to health impacts, forest fires also have a major impact on the economic, social and environmental affairs of local communities. And the biggest group that bears the impact is again women. The Women Research Institute (2016) states that women as the person in charge of domestic affairs turned out to be the most real victims in the domino effect of these forest fires. To name a few examples, women have to take care of sick family members even though they themselves are in poor health conditions. Women who are pregnant and breastfeeding have to breathe toxic air which results in low nutrition delivered to their children. If the head of the family cannot actively work because of illness, then it is the woman who must be the backbone of the family. Because they are directly affected, women have also been shown to be actively involved in various efforts to extinguish forest fires. Starting from technical forest fires to informal advocacy against companies that have forest concession permits. However, in various decision-making forums between the government and companies related to forest concessions that involve elements of the community, women’s groups are often not involved, so women’s aspirations and interests are not taken into account. In fact, in forest management and utilization, men and women have different roles and knowledge, so that their involvement is very important to realize proper governance. This study intends to explore and identify the extent to which women and their groups are involved in forest and environmental conservation efforts in Riau. The information obtained later is expected to be able to explain how the cultural and social constructs of society in supporting the involvement of women in these efforts. Including how these cultural constructs ultimately influence the government’s decision to involve women’s groups. Keywords: Ecofeminism, Forestry, Conservation, Forest fires